Surgical treatment of chronic aortoiliac occlusion - Lucas,Márcio Luís (2015)
BACKGROUND: Chronic aortoiliac occlusion (CAIO) is a significant cause of lower limb ischemia and is often found in young patients who smoke. OBJECTIVE: To review recent results achieved treating CAIO patients with open surgery. METHODS: From November 2011 to April 2014, 21 patients with CAIO were treated at the Santa Casa de Misericórdia, Porto Alegre, Brazil. Demographic data, comorbidities, clinical presentation and surgical results were analyzed. RESULTS: Eleven women and ten men were treated with direct aortic bypass (DAB; n=18) or with extra-anatomic bypass (EAD; n=3). Mean age was 53.7 ± 7.3 years (range: 43-79 years) and all patients smoked. Thirteen patients (62%) had critical ischemia. Six of the patients treated with DAB (33.4%) also required additional revascularization (3 renal and 3 femoropopliteal procedures). Perioperative mortality was zero. Four patients (22.2%) suffered transitory renal dysfunction, but only one patient (5.6%) required hemodialysis. Median follow-up time was 17 months (range: 2-29 months) and there was just one late death, from ischemic heart disease, 7 months after the surgery on the abdominal aorta. CONCLUSIONS: Aortic reconstruction is a safe method for treating patients with CAIO, with low perioperative morbidity and mortality rates.